(untitled) - UMAMI M, KHOIRUL (Language Horizon: Journal of Language Studies, 2013)
Margaret Thatcher adalah Perdana Menteri wanita di Inggris yang terlama yang dijuluki sebagai the iron lady (wanita bertangan besi). Di dalam beberapa percakapan yang diucapkan, ia menggunakan fitur fitur bahasa yang biasa dipakai oleh wanita. Selain menjadi seorang Perdana Menteri yang harus memiliki sifat tegas dan berwibawa di setiap ucapannya, dia juga masih memiliki sifat feminim yang ditunjukkan dengan penggunaan fitur fitur bahasa wanita ketika dia melakukan tugas tugasnya di rumah sebagai seorang ibu. Seperti terlihat dalam skrip film The Iron Lady, sebuah film biografi tentang dirinya, dapat dilihat fitur fitur bahasa wanita yang digunakan berdasarkan teori Lakoff tentang fitur bahasa wanita. Ditemukan ada Sembilan fitur bahasa yang digunakan oleh Margaret, yaitu lexical hedges or fillers, tag question, declaratives, empty adjectives, intensifiers, superpolite form, avoidance of strong swear words, hypercorrect grammar, dan emphatic stress. Kata kunci: fitur bahasa wanita, bahasa wanita, ucapan Abstract Margaret Thatcher is the longest woman Prime Minister in Britain who called as the iron lady. She is able to use women’s speech features in some of her conversations. In spite of becoming Prime Minister who has to have power and authority in each of her speeches, she also has femininity side as shown in her using of women’s speech features when she is in house doing her duties as a mother. As seen in the script of The Iron Lady movie, a biographical movie of her, it can be seen her speech features based on Lakoff’s theory of women’s speech features. It is found that there are nine speech features that she uses, they are lexical hedges or fillers, tag question, declaratives, empty adjectives, intensifiers, superpolite form, avoidance of strong swear words, hypercorrect grammar, and emphatic stress. Keywords: woman’s speech features, women’s language, utterances